Diversity, seasonal abundance, and environmental drivers of chaetognath populations in North Inlet Estuary, South Carolina, USA - Sarah E. Stone; Joshua P. Stone (Ecology and Evolution, 2023)
Abstract Chaetognaths (Phylum: Chaetognatha) are one of the most abundant phyla of zooplankton worldwide and play an important role in marine trophic interactions. Although the role of chaetognaths in global ecosystems is well understood, the spatial variation and environmental drivers of estuarine chaetognath populations is poorly understood. To provide the first known record of chaetognath species composition in a coastal estuary in the south‐eastern USA, chaetognaths were identified and quantified from zooplankton samples collected on a monthly basis in 2019 and 2020 from North Inlet Estuary in South Carolina. Parasagitta tenuis was the most abundant species of the five found, making up 33% of total abundance. The egg presence of these chaetognaths was further analyzed to gauge reproductive cycles. Abundance and egg presence were compared with surface and bottom measurements of temperature, salinity, and dissolved oxygen levels to determine the driving abiotic factors behind chaetognath's seasonal variability and reproductive cycles. Temperature, salinity, and dissolved oxygen all had low (r < ±.29), non‐significant correlations with abundance. Chaetognath egg production was most significantly associated with dissolved oxygen (p < .001) and seasonal changes in temperature (p < .001). Our initial findings indicate the continued abundance of chaetognath in a local estuary are dependent on abiotic factors that are strongly influenced by a changing climate.